Tumor suppressive function of microRNA-192 in acute lymphoblastic leukemia (Biomolecules and Biomedicine, 2017)
Non-coding RNAs play a critical role in gene regulation in cancer cells. Reduced expression of microRNA-192 (miR-192) has been detected in many cancers. In this study, we investigated the role of miR-192 in cell proliferation and cell cycle control in NALM-6 cell line, a model of acute lymphoblastic leukemia (ALL). Cell cycle analysis by DNA content using propidium iodide staining and cell apoptosis analysis using Annexin V assay were carried out. Cell proliferation changes were monitored using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. In addition, the relative changes in P53, BAX, CASP3, and BCL-2 gene expression were determined by quantitative reverse transcription PCR. Overexpression of miR-192 resulted in cell proliferation arrest in ALL cells. After 72 and 96 hours of transduction, apoptosis was significantly increased in the cells transduced with miR-192-overexpressing virus compared with control cells. The expression of P53, BAX, and CASP3 increased after 48 hours of transduction in miR-192-overexpressing cells, but no change was observed in BCL-2 expression. The G0/S and G1/S ratio changed to 7.5 and 4.5, respectively, in the cells overexpressing miR-192 compared with controls. The results of our study suggest, for the first time, tumor suppressive effects of miR-192 in ALL cells.